Effect of speed, agility and quickness (SAQ) exercises on the development of physical abilities of soccer referees in Iraq - Ghadban Ibrahim, Haider; Ghani Hussein, Muhammad (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The aim of this study was to develop exercises specifically designed to enhance the physical and motor abilities of football referees. Additionally, it sought to identify the percentage of development in the studied variables. The researchers deliberately chose to use the experimental method with a single experimental group and conducted two tests before and after, which is more suitable for achieving the objectives of the research. The research sample comprised 20 referees, with 10 being yard referees and 10 assistant referees. The following tests were used: Speed Test for Arena Referees (FIFA), Speed Endurance Test for Arena Referees, Agility Test for Assistant Referees (Coda): (FIFA), Speed Test for Assistant Referees (FIFA), Speed Endurance Test for Assistant Referees (FIFA). The researchers utilized the statistical software package SPSS to extract and analyze the results of the research variables. Statistically significant differences were observed between the pre and post-tests of the research sample, favoring the post-tests, indicating the effectiveness of the training program utilizing SAQ exercises in developing various physical and motor abilities among the individuals. The results clearly demonstrated the positive impact of this training approach. Notably, the referees exhibited a notable level of enthusiasm during the exercises, reflecting their eagerness to engage in a training method that was novel to them, which was evident in the differences observed in the results.